2003
DOI: 10.1002/glia.10200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying dexamethasone inhibition of iNOS expression and activity in C6 glioma cells

Abstract: The synthetic glucocorticoid dexamethasone is routinely used to stabilize patients with malignant gliomas. One putative target for glucocorticoid action is inducible nitric oxide synthase (iNOS), which is produced by the tumor cells as well as the host immune cells. In this study, we characterize the stimulatory effects of lipopolysaccharide (LPS) and the cytokine, tumor necrosis factor-alpha (TNFalpha), as well as the inhibitory effect of glucocorticoids, on iNOS gene expression and activity in C6 glioma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
(36 reference statements)
0
14
0
1
Order By: Relevance
“…For example, via post-transcriptional mechanisms, dexamethasone inhibits IL-8 mRNA and protein expression in cultured airway epithelial cells [83], inhibits inducible NOS expression and activity in C6 glioma cells [84], increases macrophage migrating inhibitory factor in rat tissues [85], and increases angiotensin-converting enzyme in primary culture of adult cardiac fibroblasts [86]. …”
Section: Molecular Action Of Glucocorticoidsmentioning
confidence: 99%
“…For example, via post-transcriptional mechanisms, dexamethasone inhibits IL-8 mRNA and protein expression in cultured airway epithelial cells [83], inhibits inducible NOS expression and activity in C6 glioma cells [84], increases macrophage migrating inhibitory factor in rat tissues [85], and increases angiotensin-converting enzyme in primary culture of adult cardiac fibroblasts [86]. …”
Section: Molecular Action Of Glucocorticoidsmentioning
confidence: 99%
“…However, isoflupredone and dexamethasone affected the proteomic profile of the endometrial fluid, although the altered proteins are different (Arlas et al, 2014). It has been demonstrated that glucocorticoids inhibit NO production in many cell types and reduce iNOS mRNA levels (Shinoda et al, 2003). Our hypothesis is that the use of isoflupredone reduces uterine NO levels.…”
Section: Introductionmentioning
confidence: 85%
“…Although additional post-transcriptional mechanisms have been shown in cell culture systems (34,35), the transcriptional pathway appears to be a major contributor to glucocorticoid inhibition of iNOS and likely other pro-inflammatory enzymes and cytokines (8–10). …”
Section: Discussionmentioning
confidence: 99%